A randomised controlled trial on whether a participatory ergonomics intervention could prevent musculoskeletal disorders. Issue 12 (16th April 2008) - Haukka, E; Leino-Arjas, P; Viikari-Juntura, E; Takala, E-P; Malmivaara, A; Hopsu, L; Mutanen, P; Ketola, R; Virtanen, T; Pehkonen, I; Holtari-Leino, M; Nykänen, J; et al.
Abstract : Objectives: To examine the efficacy of a participatory ergonomics intervention in preventing musculoskeletal disorders among kitchen workers. Participatory ergonomics is commonly recommended to reduce musculoskeletal disorders, but evidence for its effectiveness is sparse. Methods: A cluster randomised controlled trial among the 504 workers of 119 kitchens in Finland was conducted during 2002–2005. Kitchens were randomised to an intervention (n = 59) and control (n = 60) group. The duration of the intervention that guided the workers to identify strenuous work tasks and to seek solutions for decreasing physical and mental workload, was 11 to 14 months. In total, 402 ergonomic changes were implemented. The main outcome measures were the occurrence of and trouble caused by musculoskeletal pain in seven anatomical sites, local fatigue after work, and sick leave due to musculoskeletal disorders. Individual level data were collected by a questionnaire at baseline and every 3 months during the intervention and 1-year follow-up period. All response rates exceeded 92%. Results: No systematic differences in any outcome variable were found between the intervention and control groups during the intervention or during the 1-year follow-up. Conclusions: The intervention did not reduce perceived physical work load and no evidence was found for the efficacy of the intervention in preventing musculoskeletal disorders among kitchen workers. It may be that a more comprehensive redesign of work organisation and processes is needed, taking more account of workers' physical and mental resources.